Investigation of the Presence of Leptospira interrogans in Urinary and Genital Tracts of Male Goats Raised in the Semiarid Region of Brazil - Soares, Rafael Rodrigues; da Costa Barnabé, Nathanael Natércio; Júnior, João Pessoa Araújo [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; da Costa, Diego Figueiredo; Rodrigues Silva, Maria Luana Cristiny; dos Santos Higino, Severino Silvano; de Azevedo, Sergio Santos; Alves, Clebert José (Elsevier, 2023)
Leptospira sp. is a bacterium present in different environments, including those with unfavorable conditions for survival, with evidence pointing to its adaptation to the genital tract. The aim of the study was to detect Leptospira sp. using serological, molecular and bacterial techniques in samples from the genital and urinary tracts of male goats slaughtered under semiarid conditions. Forty animals destined for slaughter were sampled and, from each one, samples were taken from the urinary and genital tracts for analysis by polymerase chain reaction (PCR) and microbial culture growth, as well as serum samples for microscopic agglutination testing (MAT). Serological data showed three (7.5%) animals positive for the Pyrogenes serogroup. DNA from Leptospira sp. was detected by molecular testing in 25/120 (20.8%) of the urinary tract samples and in 23/120 (19.1%) of the genital tracts, with no statistically significant difference. A Leptospira sp. sample collected from the vas deferens was sent for DNA sequencing and showed 99% similarity with L. interrogans. Overall, 240 cultures were evaluated and, of these, 36 (15%) showed bacterial growth. Thus, Leptospira sp. organisms were present in male goats managed in an environment of adverse conditions and the spread of Leptospira sp. may be linked to venereal transmission.
Keywords: Genitourinary Tract; Goat; Isolation; Microscopic Agglutination Testing; Molecular; Small Ruminant